2020
DOI: 10.3389/fevo.2020.597450
|View full text |Cite
|
Sign up to set email alerts
|

How to Become a Generalist Species? Individual Niche Variation Across Habitat Transformation Gradients

Abstract: Species in transformed habitats, frequently labeled as environmental generalists, tend to show broader niches than species in natural habitats. However, how population niche expansion translates into changes in the niches of individual organisms remains unclear, particularly in the context of habitat transformation. Niche expansion could be a product of individuals having broader niches, greater distances among individuals’ niches, or a combination of both processes. This would challenge the traditional concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Notably, amphibians are particularly vulnerable to environmental stresses and changes due to their highly permeable skin, unshelled eggs, and low dispersal abilities [ 10 ]. Previous studies have explained how amphibians respond to environmental changes through different strategies, such as niche shift [ 11 , 12 , 13 ], phenological changes [ 2 , 14 ], and variations in morphological traits [ 7 , 15 , 16 ]. Morphological variations that, in particular, reflect a strong link between an organism’s fitness and processes in the community and ecosystem, can help us understand how amphibians respond adaptively to environmental stresses and changes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, amphibians are particularly vulnerable to environmental stresses and changes due to their highly permeable skin, unshelled eggs, and low dispersal abilities [ 10 ]. Previous studies have explained how amphibians respond to environmental changes through different strategies, such as niche shift [ 11 , 12 , 13 ], phenological changes [ 2 , 14 ], and variations in morphological traits [ 7 , 15 , 16 ]. Morphological variations that, in particular, reflect a strong link between an organism’s fitness and processes in the community and ecosystem, can help us understand how amphibians respond adaptively to environmental stresses and changes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This, combined with our findings that urban foraging is linearly linked to isotope values, suggests that both within‐ and between‐individual differences in urban foraging resulted in trophic niche expansion at the peri‐urban colonies. Liang et al (2020) reported similar findings in multiple passerine and frog species, where a combination of between‐ and within‐individual differences drove changes in trophic niche size across urban and natural populations. Several studies have found that urban diet items show distinctly different isotope values than natural diet items (Lato et al, 2021; Moreno et al, 2010; Shlepr et al, 2021), and thus likely further drives differences in isotopic values and niche sizes in urban populations.…”
Section: Discussionmentioning
confidence: 73%
“…Traits that generally promote positive responses to urbanisation include high fecundity, strong dispersal ability, behavioural flexibility, and increased tolerance and/or habituation to human presence 4 – 10 , but it is usually species dependent as to which traits are the most favourable 11 , 12 . Recently published literature shows that diet generalists tend to exhibit a positive response more often than diet specialist species in urban ecosystems 13 , 14 , as generalist species occupy broader niches that allow them to tolerate a wider array of landscapes 15 17 and to explore a variety of different food resources 8 , 18 . As the world continues to urbanise 19 , 20 , understanding the species-specific traits that allow wildlife to survive within urban habitat is vital to maintain wildlife biodiversity.…”
Section: Introductionmentioning
confidence: 99%